(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Ayurved is accepted as an oldest written medical system and it came into existence at least three thousand years before Christ. Though the present understanding of human genetics owes much to the work of Gregor Mendel but the first scientific theme on genetics had been emphasized in ancient Indian literatures. Although the technical term Genetics does not feature in Ayurved but the theme of genetics is vibrant repeatedly all classical text of Ayurved especially in Samhitas. It is an outstanding contribution of Ayurved on genetics is being described on the following heads i.e., concept of basic unit of genetics like Beeja - Beejabhag - Beejabhgavayab, concept of mutation, inheriting factors, concept of fertilization and sex determination, description of congenital diseases like Madhumeha, Arsha, Kustha etc. Prakriti and its clinical applications, therapy applied for Pumsavan kriya, how to prevent birth of a physically and mentally handicapped child. The review focuses on the various literary concept and clinical applications of genetics in Ayurved. The literary portion and clinical part of the work was done during post graduate study to established the Genetic concept in Ayurved in concordance with modern phenomena and to know the prevalence of chromosomal anomalies both autosomal and sex chromosome in patients presenting with congenital malformation. The work has been published as dissertation of post graduate study.